Elemental Aesthetics: On Artistic Experiments with Solar Energy. Issue 1 (2nd January 2018) - Engelmann, Sasha; McCormack, Derek
Abstract : In recent years, geographers and others have begun to tease out the ontological, epistemological, and ethico-political implications of thinking about and with the elemental. In this article, we contribute to this work by considering the relation between the elemental and the aesthetic. More precisely, we argue for the importance to geographical thinking of the development of an elemental aesthetics attuned to the diverse ways in which the elemental is sensed in bodies and devices of different kinds as part of the distribution of ethical and political capacities. Our argument is developed via participatory engagement with the work of contemporary artist and architect Tomás Saraceno, central to which is the ongoing attempt to craft aesthetic works that mobilize the elemental energy of the sun to generate novel modes of sensing, traveling, and living in the air. Drawing on participatory research and engagement with Saraceno's Aerocene project, we show how his work helps us reimagine distributions of the capacity to sense the elemental. In the process, we reflect on some of the ways in which these experiments can inform the shape and orientation of geographical engagements with an elemental aesthetics.